Perspectives of adults with intellectual disabilities and key individuals on community participation in inclusive settings: A Canadian exploratory study. Issue 1 (2nd January 2021) - Milot, Élise; Couvrette, Romane; Grandisson, Marie
ABSTRACT: Background: This article aims to present the results of a study on the facilitators and obstacles to community participation in inclusive settings for people with intellectual disabilities (ID) in Québec City (Canada), as perceived by adults with ID and key individuals involved in their daily lives. Method: Semi-structured interviews were conducted, followed by an inductive thematic analysis process. Results: Twenty participants shared their perspectives on the factors that influence community participation of adults with ID in inclusive settings. Overall, they revolved around physical and financial accessibility, openness of the members of the groups attended, as well as the adaptations and support provided to promote the people's active participation. Conclusions: Offering social support and interventions that truly help adults with ID create meaningful relationships is crucial. Training community members is also fundamental to creating environments where people with ID can feel that they belong.